2017
DOI: 10.1177/1947603517743545
|View full text |Cite
|
Sign up to set email alerts
|

Successful Return to Sport Following Distal Femoral Varus Osteotomy

Abstract: Objectives: Distal femoral varus osteotomy is an effective treatment for unloading valgus knee malalignment; however, there is limited evidence on the ability for patients to return to athletics following this procedure. The purpose of this study is to report the functional outcomes and return to sport for athletic patients that underwent distal femoral varus osteotomy. Methods: A consecutive series of athletic patients that had undergone distal femoral varus osteotomy for symptomatic lateral compartment overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…In that group, the rate of return to physical activity was 57.7% at a mean follow-up time of 48 months. More recently, Voleti et al 15 reported a 100% rate of return to sport at a mean time of 11 months in 13 patients who underwent DFO for unloading valgus knee malalignment. Of those patients, 9 (69.2%) had concomitant chondral, meniscal, or ligamentous procedures performed on the ipsilateral knee joint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In that group, the rate of return to physical activity was 57.7% at a mean follow-up time of 48 months. More recently, Voleti et al 15 reported a 100% rate of return to sport at a mean time of 11 months in 13 patients who underwent DFO for unloading valgus knee malalignment. Of those patients, 9 (69.2%) had concomitant chondral, meniscal, or ligamentous procedures performed on the ipsilateral knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…More research is necessary to determine whether DFO should be routinely performed in athletes with lower extremity malalignment who wish to return to physical activity, but these past 2 studies showed promising outcomes. 4 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…'nın distal femoral osteotomi ameliyatı geçiren 13 atlet hastada yaptıkları çalışmada, sporcuların ameliyat sonrası ortalama 11. ayda yaptıkları spora sorunsuz şekilde döndükleri bildirilmiştir. [27] Başka bir çalışmada ise Beyzadeoğlu ve ark., 21 hastanın 24 dizine yaptıkları osteotomi ile kombine yaptıkları yüzey kaplama artroplastisi ameliyatları sonrası, tüm hastalarında aynı düzeyde spora dönüş bildirmişlerdir. [28] Spora dönüşe katkıda bulunan en önemli faktörlerden biri de hasta motivasyonudur.…”
Section: Di̇z çEvresi̇ Osteotomi̇leri̇ Sonrasi Spora Dönüşunclassified